Hygrothermo-mechanical behaviour of layered composite plates - Thinh, Tran Ich (Vietnam Journal of Mechanics, 2002)
In this paper, a hygrothermo-mechanical behaviour of simply supported, composite layered rectangular plates is presented. The analysis is based on use of the Finite Element (FE) method and the full third-order displacement theory. Numerical examples are presented for symmetrically in-axis (0° /90° /90° /0°) and off-axis ( 45° / - 45° / -45° / 45°) layered rectangular plates.